POPULATION GROWTH EFFECTS ON TRANSPORT FACILITIES IN KADUNA SOUTH LOCAL GOVERNMENT AREA OF KADUNA STATE - Tadama, M. H.; Monday, E. D.; Garba, A.; Musa, S. M. (FUDMA Journal of Sciences, 2022)
This paper examined effect of population growth on transport facilities in Kaduna South, Nigeria. Data obtained were collected and were summarized as absolute frequencies and proportion using the simple descriptive percentage method and presented in a Histogram, Bar chart and pie chart. The study revealed that from the study area, 36.3% of the respondents indicated that infrastructure attracts the population as a result causing rapid population growth, 27.4% indicated Job opportunities, 22.2% indicated security and 14.1% indicated unemployment as the cause of the rapid population growth. Also, from the data obtained from the respondents on the effects of rapid population growth, 32.2% indicated overpopulation, 29.2 % indicated pollution, 21.8% of the respondents indicated high crime rate 16.6% indicated unemployment as an effect of the rapid population growth; The data obtained on the dominant mode of transportation in the study area, 75.2% indicated Tricycle (Keke Napep), 2.6% indicated Taxi; 2.9% bus; 7.8% indicated Bikes and 11.5% indicated all modes of transportation (Tricycle, Taxi, Bus and Bikes). Also, on the major problems of road transport, the respondents revealed that poor road system, lack of well-trained road safety personnel, bad or reckless driving from both commercial driver & private drivers, and the violation of traffic rules are the major problem. The study concluded that this research work has proven beyond doubt that population affects the transportation and its facilities Positively in the study area.
Keywords: Population; Transport; Growth; Facilities